2020
DOI: 10.1055/s-0040-1716549
|View full text |Cite
|
Sign up to set email alerts
|

Burden-of-Illness Associated with Bleeding-Related Hospitalizations in Atrial Fibrillation Patients: Findings from the Nationwide Readmission Database

Abstract: Introduction A paucity of contemporary data examining bleeding-related hospitalization outcomes in atrial fibrillation (AF) patients exists. Methods Adults in the Nationwide Readmissions Database (January 2016–November 2016) with AF and hospitalized for intracranial hemorrhage (ICH), gastrointestinal, genitourinary, or other bleeding were identified. Association between bleed types and outcomes were assessed using multivariable regression (gastrointestinal defined as referent) and reported as crude i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…This may imply that these risk factors relate to the need for more institutionalized services after discharge from the index hospitalization and potentially extending the health care resource use burden. The results of this study are consistent with another real‐world study of bleeding‐related hospitalizations in patients with atrial fibrillation, in which ICH was associated with higher odds of in‐hospital mortality, longer hospitalization length of stay, and need for postdischarge out‐of‐home care versus GI bleeding 18 . Previous studies have shown that discharge destination can provide highly predictive values and likelihood ratios for death and disability in patients with ICH 19,20 .…”
Section: Discussionsupporting
confidence: 89%
“…This may imply that these risk factors relate to the need for more institutionalized services after discharge from the index hospitalization and potentially extending the health care resource use burden. The results of this study are consistent with another real‐world study of bleeding‐related hospitalizations in patients with atrial fibrillation, in which ICH was associated with higher odds of in‐hospital mortality, longer hospitalization length of stay, and need for postdischarge out‐of‐home care versus GI bleeding 18 . Previous studies have shown that discharge destination can provide highly predictive values and likelihood ratios for death and disability in patients with ICH 19,20 .…”
Section: Discussionsupporting
confidence: 89%
“…Secondary outcomes included thrombotic event occurrence during the first five days after reversal agent administration. The five-day time frame for thrombotic events was selected as it was a time point specifically reported in ANNEXA-4 and it reduced potential surveillance bias (which can occur when outcomes are sought with differential intensity across populations or over time, or according to care setting and/or patient characteristics) associated with post-discharge thrombotic events [6,11].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, investigators in the prospective ANNEXA-4 study actively surveilled for thrombotic events, whereas clinicians in routine practice were less likely to do so, which could have biased the detection of thrombotic events against andexanet alfa. Of note, the five-day time point for thrombotic events utilized in our study was based on the time stratifications reported within the ANNEXA-4 study (< 6, 6-14, and 15-30 days after andexanet alfa administration) [11] and a recent study by Miao and colleagues [6], which demonstrated that five to six days is the median hospital length of stay for atrial fibrillation patients experiencing an intracranial hemorrhage. Third, based upon our study's inclusion criteria, our findings are most applicable to an apixaban-or rivaroxaban-associated intracranial hemorrhage population with baseline GCS scores ≥ 8 and hematoma volumes ≤ 60 mL managed in the USA.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…У пациентов, принимающих ПОАК, ниже риск смертельных и жизнеугрожающих, в т.ч. внутричерепных и внутримозговых, кровотечений, оказывающих серьезное влияние на прогноз, и чаще приводящих к инвалидности и летальному исходу по сравнению с варфарином [24].…”
unclassified